MEMBANGUN SISTEM KOMPUTERISASI SURVEY PERIZINAN SEBAGAI SISTEM PENDUKUNG “SIPINTER” DI DPMPTSP KOTA SURAKARTA BERBASIS WEBSITE - Muhammad Azhari; Firdhaus Hari Saputro Al Haris; Hardika Khusnuliawati (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2019)
The process of making a survey schedule in DPMPTSP Surakarta is still done manually. It used recording of survey schedule from agenda book. The process of making this survey schedule resulted ineffective and inefficient services. The aims of research is to create computerized system survey based on a website. The method used interviews, observation, literature review, documentation and waterfall modelling. This study produced a computerized survey system based on website for DPMPTSP Surakarta. This system is expected to accelerate and to facilitate employees in making survey schedules. The design of a computerized survey system includes managing survey schedule data, managing data from the results of reviews and managing user data. System testing used alpha and beta testing. Alpha testing by using black box testing method shows that 5 test cases and 19 test items. Thus, it can be concluded that the computerized survey system is 100% fulfilled or it can run as expected. The beta test results are done by calculating the overall average of each statement compared to the Likert Scale score category table. Therefore, it also can be concluded that the average of the results of testing acceptance is 90.3%. it means that all users receive the application properly.